A Numerical Investigation on the Effect of Gas Pressure on the Water Saturation of Compacted Bentonite-Sand Samples. (27th December 2017) - Liu, Jiang-Feng; Song, Shuai-Bing; Liu, Jian; Huang, Bing-Xiang; Cao, Xu-Lou; Zhang, Kai; Skoczylas, Frédéric
Abstract : In deep geological disposal for high-level radioactive waste, the generated gas can potentially affect the sealing ability of bentonite buffers. There is a competition between water and gas: the former provides sealing by swelling bentonite, and the latter attempts to desaturate the bentonite buffer. Thus, this study focused on numerically modelling the coupling effects of water and gas on the water saturation and sealing efficiency of compacted bentonite-sand samples. Different gas pressures were applied to the top surface of an upper sample, whereas the water pressure on the bottom side of the lower sample was maintained at 4 MPa. The results indicated that gas pressure did not significantly affect the saturation of the bentonite-sand sample until 2 MPa. At 2 MPa, the degree of water saturation of the upper sample was close to 1.0. As the gas pressure increased, this influence was more apparent. When the gas pressure was 6 MPa or higher, it was difficult for the upper sample to become fully saturated. Additionally, the lower sample was desaturated due to the high gas pressure. This indicated that gas pressure played an important role in the water saturation process and can affect the sealing efficiency of bentonite-based buffer materials.